The Translation of Indonesian Cultural Terms into English of the “Battle of Surabaya” Movie - Bagus Yogi Martendi; Teguh Setiawan; Ashadi Ashadi (Universitas Sanata Dharma, 2022)
This study aims to identify and describe the translation of Indonesian cultural terms in the film Battle of Surabaya. It did not intend to pinpoint the exact translation technique used. The animated history of Indonesia and the variety of the language used in the movie, such as Dutch, English, Japanese, Indonesian, and local, motivated the researcher to conduct the research. The research method used mixed-method and translation theory as a ground theory for analyzing the data. The analysis found that 24 vocabularies contain Indonesian culture-each cultural term spread in every aspect. Socio-culture found 17 data or 71% of the total existing data; Material culture only found 1 data, Ecology 3 data, Organization 2 data, Gesture or habits also 1 data. The difference in translating cultural terms was only to equate equivalence in meaning between ST and TT. Bringing cultural aspects in various ways is the same as appreciating a culture, but the way to show it and transfer it becomes a challenge for the translator. The true meaning of a cultural term may not be fully conveyed due to a lack of data or only communicated to each other in a cultural group. It can be solved if the cultural term has a glossary and the translator uses it. This study also found that foreign cultures that have been in the local culture for too long can grow and become part of the local culture itself.